Saccharomyces cerevisiae additions normalized hemocyte differential genes expression and regulated crayfish (Procambarus clarkii) oxidative damage under cadmium stress - Yaru Yang; Shuaidong Li; Yumin Zhu; Litao Che; Qifan Wu; Shijun Bai; Guocheng Shu; Xianming Zhao; Peng Guo; Salma A. Soaud; Nianzhen Li; Mengling Deng; et al. (Scientific Reports, 2023)
Abstract Because China produces the most crayfish in the world, safe solutions must be improved to mitigate the risks of ongoing heavy metal stressors accumulation. This study aimed to use Saccharomyces cerevisiae as a bioremediation agent to counteract the harmful effect of cadmium (Cd) on crayfish (Procambarus clarkia). Our study used three concentrations of S. cerevisiae on crayfish feed to assess their Cd toxicity remediation effect by measuring total antioxidant capacity (TAC) and the biomarkers related to oxidative stress like malondialdehyde (MDA), protein carbonyl derivates (PCO), and DNA–protein crosslink (DPC). A graphite furnace atomic absorption spectroscopy device was used to determine Cd contents in crayfish. Furthermore, the mRNA expression levels of lysozyme (LSZ), metallothionein (MT), and prophenoloxidase (proPO) were evaluated before and following the addition of S. cerevisiae. The results indicated that S. cerevisae at 5% supplemented in fundamental feed exhibited the best removal effect, and Cd removal rates at days 4th, 8th, 12th, and 21st were 12, 19, 29.7, and 66.45%, respectively, which were significantly higher than the basal diet of crayfish. The addition of S. cerevisiae increased TAC levels. On the other hand, it decreased MDA, PCO, and DPC, which had risen due to Cd exposure. Furthermore, it increased the expression of proPO, which was reduced by Cd exposure, and decreased the expression of LSZ and MT, acting in the opposite direction of Cd exposure alone. These findings demonstrated that feeding S. cerevisiae effectively reduces the Cd from crayfish and could be used to develop Cd-free crayfish-based foods.